ROLE PLAY GAMES IN THE EDUCATIONAL PROCESS (Proceedings of International Educators Conference, 2022)
Role-playing should be content-driven, consistent with learning objectives, and relevant to real-world situations so that students understand how to use it. Role-play exercises encourage students to think more critically about complex and controversial issues and see situations from a different perspective. Role-playing games are used as a type of activity related to the organization of leisure and as an activity related to the pedagogical process.